Genetic and phenotypic characterization of African goat populations to prioritize conservation and production efforts for small-holder farmers in sub-Saharan Africa - Huson, Heather J.; Sonstegard, T.S.; Silverstein, J.; Woodward-Greene, M. Jennifer; Masiga, C.; Muchadeyi, F.C.; Rees, J.; Sayre, B.; Elbetagy, A.; Rothschild, Max F.; Mujibi, F.D.N.; Okeyo Mwai, Ally; et al. (American Society of Animal Science, 2014)
Food production systems in Africa depend heavily on the use of locally adapted animals. Goats are critical to small-holder farmers being easier to acquire, maintain, and act as scavengers in sparse pasture. Indigenous goats have undergone generations of adaptation and genetic isolation that have led to great phenotypic variation. These indigenous goats serve as a genetic reservoir for the identification of genes important to environmental adaptation, disease resistance, and improved productivity under local conditions. The immediate goal is to characterize African goat populations to prioritize conservation and production efforts and to develop genomic tools for use in selective breeding programs. We have established a standardized phenotypic scoring system to characterize goats including geographical information data, body measurements, photo characterization, and DNA. To date, 2,443 goats from 12 countries, representing 46 breeds have been sampled. Using the 50K goat beadchip, we report parameters of population structure of 620 African goats.